Actors of the Cultural Fennomania and Their Contribution to Finnish National Movement - D. E. Kolesnikov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article examines the first stage of the Finnish national movement (Fennoman movement) which took place at the first half of the 19th century and is named as the “cultural fennomania” in historical literature. It analyzes the role of Elias Lönnrot and Johan Ludvig Runeberg in the Fennoman movement. At the end of the article the conclusion is drawn that J.V. Snellman, E. Lönnrot and J.L. Runeberg made great contribution to the process of formation of the Finnish national-consciousness.